How morphological surface parameters are correlated with electrocatalytic performance of cobalt-based nanostructures - Naseri, Naimeh; Ţălu, Ştefan; Kulesza, Slawomir; Qarechalloo, Shervin; Achour, Amine; Bramowicz, Miroslaw; Ghaderi, Atefeh; Solaymani, Shahram (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] •Co nanostructures were deposited on pure TNAs by electrodeposition technique.•Autocorrelation functions of 3-D surface texture of TNAs/Co were presented.•XRD indicated that the fabricated TNAs were in anatase and rutile phase.•Correlation between morphological surface and PEC performance was established. To overcome recent energy and environment challenges, developing efficient and low cost photocatalysts are unavoidable. In this context, design of semiconductor nanostructures modified with earth abundant co-catalysts for water splitting reactions requires well engineered and controlled process to optimize surface interface and maximize nanocomposite system efficiency. Here, TiO2 nanotube were synthesized electrochemically and decorated with cobalt based nanostructure co-catalyst for water oxidation reaction using low cost and scalable electro-deposition approach. By changing deposition parameters and complete studying on samples surface morphology and related statistical analysis data, correlation between all morphological parameters and photoelectrochamical activity of correspondence photoanode was illustrated for the first time. Based on SEM analysis and surface analysis data as well as catalytic performance investigation, nanotubes decorated with Co nanoparticles at 0.1mAcm−2 deposited for 2000s presented the best performance with most isotropic surface. Results suggested that by tuning deposition parameters surface structural parameters like fractal dimension, corner frequency, roughness and feature shape and size can be engineered completely. Moreover, X-ray diffraction data along with Rietveld method revealed coexistence of anatase, rutile and Ti2O3 phases in the photoanode while poor crystallinity of grown cobalt based nanostructures was confirmed.